Літописні Бакота і Пониззя у Середньому Подністров’ї - Маярчак, С.П. (Археологія, 2009)
У статті узагальнено основні здобутки та окреслено нові перспективи історичних та археологічних студій літописного міста Бакота і його округи, запропоновано нове бачення окремих моментів їхнього минулого. Статья посвящена вопросам, связанным с развитием древнерусского города Бакота и исторической области Понизье. В начале ХІІІ в. в пределах Галицкой земли — Среднем Поднестровье — проходил процесс формирования природно-исторической области Понизье и удельного княжества с центром в городе Бакота (теперь затопленное село Каменец-Подольского района на Хмельнитчине). Монгольское нашествие и покорение завоевателям Среднего Поднестровья затормозили, внесли коррективы, но не остановили этот процесс полностью. Понизье было древним интегрирующим ядром Подолья, историю становления которого надо начинать с начала ХІІІ в., когда формировалось Понизье. Возвышению Бакоты способствовала совокупность нескольких факторов, среди которых особенно важен географический. Упадок Бакоты был связан с целенаправленной политикой иностранных феодалов на снижение ее роли в регионе, как опасного для них политического центра с древними самостоятельными традициями. В статье уточнены границы Понизья, выяснена история изучения бакотских древностей древнерусского времени, обобщены мнения исследователей о названиях «Бакота», «Подолье» и «Понизье». The article is devoted to the matters related to the development of Ancient Rus city Bakota and historic region Ponyzzya. At the beginning of the 13th c. within the borders of Halych Lands, in the Dnister River middle region, a process of shaping of natural and historic region Ponyzzya and appanage principality with the centre in Bakota city (now a flooded village in Kamyanets-Podilskyi Region of Khmelnytska Oblsat) was ongoing. Mongol invasion and subjection to conquerors of the Dnister River middle region hindered, amended, but did not entirely stopped this process. Ponyzzya was an ancient integrating core of Podillya, history of development of which should be traced from the 13th c. when Ponyzzya was forming. Rise of Bakota was promoted by a set of several factors, among which a geographical one was the most important. Decline of Bacota was caused by teleological politics of foreign feudal lords aiming at diminishing its role in the region as a dangerous political centre with old independent traditions. The \ borders of Ponyzzya are specified in the article, a history of study of Bakota antiquities of Ancient Rus period are ascertained, and the researchers’ opinions on the names Bakota, Podillya, and Ponyzzya are generalized.